How is better to control corruption inside of the Administration? Is it possible and convenient that an audit body have, for example, sanctioning attributions? And if so, under which parameters? - Espinosa-Saldaña Barrera, Eloy (2020)
In this paper, the author analyzes the sanctioning power of audit bodies in Peru, and so the constitutionality parameters that they have. In that line is determined that, even when fight against corruption is a legitimate aim for giving sanctioning power to some administrative bodies, the constitutional parameters and the respect for rights of the governed should always be considered.